Pendampingan Pembentukan Karakter Peduli Lingkungan bagi Pelajar Melalui Pengelolaan Sampah - Rido, Rido Kurnianto; Nurul, Nurul Iman; Katni (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract The indifferent attitude of elementary school age children towards the surrounding environment due to their tendency to play gadgets and online games requires efforts to cultivate environmentally caring characters by utilizing waste management programs from an economic and educational perspective. This program aims to overcome the problems of target partners, namely: diverting non-productive activities into positive and productive activities by honing children's sensitivity to the surrounding environment; as well as increasing the work ethic and enthusiasm for learning of 30 children who are members of the waste soldiers. The method used in this program is empowering the target community through intensive assistance in the form of work ethic development and tutoring through study houses and literacy corners. Work ethic development is carried out through instilling the values ​​of discipline and a culture of hard work through class explanations and socialization. Meanwhile, increasing the target partner's enthusiasm for learning is carried out through guidance and additional lessons at home. Coaching and learning activities are guided by coaching and learning modules that have been previously designed by the service team. Keywords: Character, Environment, Garbage, Early Age. Abstrak Sikap acuh anak usia sekolah dasar terhadap lingkungan sekitarnya yang disebabkan kecenderungan bermain gadget dan game online memerlukan usaha dalam penanaman karakter peduli lingkungan dengan memanfaatkan program pengelolaan sampah perspektif ekonomi dan edukasi. Program ini bertujuan untuk mengatasi permasalahan mitra sasaran, yakni: mengalihkan kegiatan non produktif menjadi kegiatan positif dan produktif dengan mengasah sensitifitas anak terhadap lingkungan sekitar; serta meningkatkan etos kerja dan semangat belajar 30 anak yang tergabung dalam prajurit sampah. Metode yang dipergunakan dalam program ini adalah pemberdayaan masyarakat sasaran melalui pendampingan intensif dalam bentuk pembinaan etos kerja dan bimbingan belajar melalui rumah belajar serta pojok literasi. Pembinaan etos kerja dilakukan melalui penanaman nilai-nilai disiplin dan budaya kerja keras melalui penjelasan dan sosialisasi kelas. Sedangkan peningkatan semangat belajar mitra sasaran dilakukan melalui bimbingan dan tambahan pelajaran di rumah belajar yang dikondisikan. Kegiatan pembinaan dan pembelajaran dipandu dengan modul pembinaan dan pembelajaran yang telah didesain sebelumnya oleh tim pengabdian. Kata Kunci: Karakter, Lingkungan, Sampah, Usia dini.